THE LINGUISTIC ADAPTION IN AN IMMIGRANT LANGUAGE SETTING IN MAKASSAR, INDONESIA - Andi Samsu Rijal; Andi Mega Januarti Putri; Sulviana Sulviana (Lire Journal (Journal of Linguistics and Literature), 2021)
Historically, immigrants have been living and interacting with local people and others in Makassar from 2014 until today. These interactions result from unique way communication, how these immigrants choose a certain language to communicate with each other. This article mainly aimed to describe how was the language used among immigrant in Makassar and how was the language choice occurred in the interaction of immigrant with local people. The data were collected through observation on the recorded and transcribed conversation and interviews some of the participants to confirm how and why they used certain language during the conversation by using the sociolinguistics approach. These interactions which use some language variation or dialects can be called a linguistics adaptation as the effect of language contact situation. In their early presence that immigrants used English (Eng) and Indonesia language (IL) formally to communicate with IOM staff, UNHCR staff, among immigrants, teachers and social workers, but when they have access to live longer in Makassar, they interact with Makassar people freely and they use various languages such as Makassar language (ML), Indonesian language by Makassar Malay language (MML) dialect known as trade Malay language, or sometimes used English as their language code choice. MML was mostly used compared to another language by those immigrants in some public area in Makassar. The using of MML by immigrants was a linguistic adaptation to the target language.